Quality Management-Based Strategies For Improving Al-Qur’an Hadith Learning - Silvia Jauharotul Aini; Widya Andriyani (STAI Al-Mas'udiyah, 2025)
This study aims to analyze strategies for improving the quality of Islamic education in the teaching of Al-Qur’an Hadith at MTs Al-Ishlah, Tanjung Jabung Timur. In the context of globalization, Qur’an-Hadith learning faces challenges related to low student engagement, limited contextual understanding, and the persistence of conventional teaching approaches. However, previous studies have not sufficiently explored integrative and context-based quality improvement strategies in rural madrasah settings, particularly those combining managerial and pedagogical dimensions. This study employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that quality improvement strategies are implemented systematically through three interconnected stages: participatory planning involving institutional stakeholders, active and contextualized learning practices integrating religious habituation, and comprehensive evaluation combining cognitive, affective, and behavioral assessments. These strategies are supported by strong institutional commitment, teacher collaboration, and the development of a consistent religious culture. This study contributes by proposing a contextual quality improvement framework based on integrated managerial practices and religious values, which can serve as a reference for similar madrasah contexts.